Peran Guru dalam Implementasi Pendidikan Karakter untuk Mengatasi Masalah Bullying di Madrasah Ibtidaiyah - Silawati, Silawati; Hidayati, Dian (Academy of Education Journal, 2024)
Bullying is a social behavior that often occurs in schools. Bullying can also involve students as perpetrators and victims. Bullying also has some negative repercussions for both the victim and the perpetrator himself. If this type of bullying occurs, then the role of the teacher is needed so that the teacher can identify and overcome it. The purpose of this study was to determine the role of teachers in the implementation of character education to overcome bullying. This research method uses qualitative research methods with a case study approach. From this study, it is also known that there are several types, factors, and impacts or consequences felt by students due to bullying behavior carried out. These three aspects can be a guideline for teachers to analyze and formulate strategies to solve these problems, one of which is through the application of character education. It can be seen that the role of teachers in the implementation of character education for students is to guide or provide advice and direction, as well as develop students in order to overcome situations or problems of bullying so as to minimize the occurrence of bullying at school. Teachers play an important role in applying moral values to shape student character, especially in elementary school students, because students in this age group easily imitate the behaviors and actions they see. Therefore, in its implementation, teachers and parents must work together to achieve character building through the application of character values.